PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS VII.C SMP NEGERI 1 SINABOI SATU ATAP TAHUN PELAJARAN 2015/ 2016 - Nova Oktarita; Evi Suryawati; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning results of the IPA through the application of cooperative learning model type NHT in Grade VII. SMP Negeri 1 c Sinaboi one stop Lessons Year 2015/2016. This research was conducted in Class VII. SMP Negeri 1 c Sinaboi one roof Sinaboi Rokan Hilir in even-numbered years semester lesson 2015/2016. The subject of research is the grade 1 Land Junior Sinaboi one roof Sinaboi Rokan Hilir totalling 25 students consisting of 12 male students and female students. Based on the results of the Research Action class (PTK) and the application of Cooperative learning, NHT Type absorption cycle I by students on average 65.2 with category II cycle less on average power serapnya be 73.6 by category either. Ketuntasan Individual students in cycle I, by 60% and cycle II amounted to 88%.Classical Ketuntasan on cycle I don't thoroughly i.e. by 40% and in cycle II not completely 12%. Student activity on the cycle of the cycle I with average 73.2% category both on cycle II with an average of 95.2% by category. The activity of the teacher in the cycle I with average 65.75% categories good, cycle II with an average of 94.7% category. Group Award at the cycle I to five groups awarded a group of good, very good and super. Group I was 14 with good predicate, group II mean 12 with good, group III was 18 with excellent, Group IV mean 5 with good and Group V 28 average with super. While on cycle II to five groups awarded a group of good, very good and super. Group I was 20 with excellent, group II was 20 with excellent, group III 22 average with excellent, Group IV average 26 with super and Group V 26 average with super. Cooperative learning model by applying type NHT can improve learning outcomes grade VII. SMP Negeri 1 c Sinaboi one stop Lessons Year 2015/2016.Key Words: The Results Of The Study, Cooperative Learning, Kooperati Type Numbered HeadsTogether (NHT)